The Leadership of School Administrators Affecting the Happiness in the Workplace of Teachers in Schools under Rayong Primary Educational Service Area Office 2 - Putkaew, Suttinun; รักษนคร กุลจิรา; คงเที่ยง สมศักดิ์ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
The objectives of this research were 1) To study the leadership of school administrators. 2) To study the happiness in the workplace of teachers. 3) To study the relationship between the leadership of school administrators and the happiness in the workplace of teachers. 4) To study the leadership of school administrators affecting the happiness in the workplace of teachers under Rayong Primary Educational Service Area Office 2. The sample of 285 teachers from schools under Rayong Primary Educational Service Area Office 2 was selected, with the sample size calculated based on the Taro Yamane (1967) table. Research instrument was questionnaire with an IOC range of 0.8-1.0 and a reliability of .93. The statistics for analyzing data were frequency, percentage, mean, standard deviation, Pearson’s product moment correlation and multiple regression analysis. The results were: 1) The leadership of school administrators both overall and in each individual aspect was at a high level. 2) The happiness in the workplace of teachers in overall was at a high level, and in each individual aspect was at a high to highest level. 3) The relationships between the leadership of school administrators and the happiness in the workplace of teachers was positively at a high level (r = .614) with statistically significant at the .01 level. 4) The leadership of school administrators, participative leadership affecting the happiness in the workplace of teachers with statistically significant at the .01 level, while task-oriented leadership affecting the happiness in the workplace of teachers with statistically significant at the .05 level. The predictive the happiness in the workplace of teachers under Rayong Primary Educational Service Area Office 2 at 40.32 percentile. The predictive equations were as follows; The predictive equation in the form of raw scores: Y = 2.728 + .285 x3 + .128 x4 The predictive equation in the form of standard scores: Zy = .466Zx3 + .199Zx4